ANALISIS SWOT PADA PEMBINAAN PRESTASI CABANG OLAHRAGA HOCKEY INDOOR DI LAMPUNG - Haida Dwi Mustika; Candra Kurniawan; Riyan Jaya Sumantri; Joan Siswoyo (STKIP Subang, 2026)
This study aims to analyze the strengths, weaknesses, opportunities, and threats in the development of indoor hockey athlete performance in Lampung and to formulate development strategies using a SWOT analysis approach. The research employs a descriptive qualitative method, involving administrators, coaches, and athletes as subjects. Data were collected through interviews, observations, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that the main strengths of the athlete development program lie in the high motivation of athletes and strong teamwork. However, based on interviews and field observations, facilities and infrastructure remain limited and do not meet standard requirements, making them a major weakness in the development process. Additionally, the limited number of athletes and lack of competitive experience pose significant challenges. On the other hand, there are opportunities in the form of increasing public interest following achievements in competitions. Meanwhile, the main threat is the low popularity of the sport, which leads to minimal sponsorship and funding support. Based on the SWOT analysis, it is necessary to implement more targeted development strategies, including improving facilities and infrastructure, strengthening organizational management, and expanding opportunities to participate in competitions in order to optimally enhance athlete performance.